THE ROLE OF ESTABLISHING LEGISLATION IN HANDLING SOCIAL CONFLICT - Anang Puji Utama (RADJA PUBLIKA, 2024)
Society is a group of individuals or groups, each of whom has an interest. These various interests have the potential to cause clashes which result in the emergence of conflict in society. Law in the form of statutory regulations can bring together these various interests in a forum to formulate collective agreements which ultimately take the form of norms. The meeting took place in the process of forming legislative regulations whichwas carried out in an open and participatory manner. This effort can play a role in handling conflict in society. This article examines the process by which legislative regulations can play a role in preventing and resolving conflictsin society. The results of research conducted through research and analysis of literature found that the process of forming good laws and regulations by implementing openness and comprehensive participation can play a role incontrolling conflict in society.